Effects of written corrective feedback and language aptitude on verb tense accuracy. (November 2019) - Benson, Susan; DeKeyser, Robert
Most second language researchers agree that there is a role for corrective feedback in second language writing classes. However, many unanswered questions remain concerning the linguistic features to target and the type and amount of feedback to offer. This study examined essays by 151 learners of English as a second language (ESL), in order to investigate the effect of either direct or metalinguistic written feedback on errors with the simple past tense and the present perfect tense. This inquiry also considered the extent to which learner differences in language-analytic ability (LAA), as measured by the LLAMA F, mediated the effects of these two types of explicit written corrective feedback. Learners in both feedback groups were provided with corrective feedback on two essays whereas the control group received general comments on content. Learners in all three groups then completed two additional writing tasks to determine whether or not the provision of corrective feedback led to greater gains in accuracy compared to no feedback. Both treatment groups performed better than the comparison group on new pieces of writing immediately following the treatment sessions, yet direct feedback was more durable than metalinguistic feedback for one structure, the simple past tense. Participants with greater LAA proved more likely to achieve gains in the direct feedback group than in the metalinguistic group, whereas learners with lower LAA benefited more from metalinguistic feedback.